Athletic trainer burnout: A systematic review of the literature - Oglesby, L. W.; Gallucci, A. R.; Wynveen, C. J. (Journal of Athletic Training, 2020)
Objective: To identify the causes, effects, and prevalence of burnout in athletic trainers (ATs) identified in the literature. Data Sources: EBSCO: SPORTDiscus and OneSearch were accessed, using the search terms athletic trainer AND burnout. Study Selection: Studies selected for inclusion were peer reviewed, published in a journal, and written in English and investigated prevalence, causes, effects, or alleviation of AT burnout. Data Extraction: The initial search yielded 558 articles. Articles that did not specifically involve ATs were excluded from further inspection. The remaining 83 full-text articles were reviewed. Of these 83 articles, 48 examined prevalence, causes, effects, or alleviation of AT burnout. An evaluation of the bibliographies of those 48 articles revealed 3 additional articles that were not initially identified but met the inclusion criteria. In total, 51 articles were included in data collection. Data Synthesis: Articles were categorized based on investigation of prevalence, causes, effects, or alleviation of burnout. Articles were also categorized based on which subset of the athletic training population they observed (ie, athletic training students, certified graduate assistants, high school or collegiate staff members, academic faculty). Conclusions: Burnout was observed in all studied subsets of the population (ie, students, graduate assistants, staff, faculty), and multiple causes of burnout were reported. Suggested causes of burnout in ATs included work-life conflict and organizational factors such as poor salaries, long hours, and difficulties dealing with the "politics and bureaucracy" of athletics. Effects of burnout in ATs included physical, emotional, and behavioral concerns (eg, intention to leave the job or profession).